STUDIES ON CHELONUS SP. THE PARASITE OF THE COCONUT MOTH BATRACHEDRA ARENOSELLA WALKER - Wily A. Baringbing; Bariyah Baringbing (International Coconut Community, 1997)
An experiment was conducted at a coconut pest laboratory at Nita, elevation 250 m, Sikka regency, Flores island, province of East Nusa Tenggara, to study mass production of Chelonus parasite by using Phthorimaea operculella Zeller as its host, in an effort to control the coconut moth, Batrachedra arenosella Walker, biologically. Results of the experiment showed that the parasite could be produced in laboratory by using P. operculella as the host and a 10% solution of honey as food for both parasite and the adult host. A female parasite gave an average of 14 offspning during their lives with a sex ratio of 2.27:1, between male and female. The sex ratio of the same parasite in the field with B. arenosella as its host was 1:1. The incubation period of the parasite in laboratory was 26 days for males and 27 days for females. The sex ratio of the moth in the field as 1: 1.26.